The relationship between occupational stress, job burnout and quality of life among surgical nurses in Xinjiang, China - Xue Li; Ting Jiang; Jian Sun; Lingyun Shi; Jiwen Liu (BMC, 2021)
Abstract Background Nursing is a high-risk occupation that involves exposure to stress. The physical and mental health of nurses is directly related to the quality of medical services, so the quality of life of nurses cannot be ignored. This study is a Chinese nursing study that investigated occupational stress, job burnout, and quality of life of surgical nurses in Xinjiang, China. Methods This study employed the cluster random sampling method and carried out a questionnaire survey among 488 surgical nurses from five hospitals from May 2019 to September 2019. The study analyzed the relationship between occupational stress, job burnout and quality of life. The Effort-Reward Imbalance questionnaire (ERI), Maslach Burnout Inventory General Survey (MBI-GS) and the 36-item Short Form Health Survey (SF-36) were used to evaluate occupational stress, job burnout and quality of life among surgical nurses. Results A total of 550 questionnaires were distributed in this study, and 488 were retrieved, with an effective recovery rate of 88.73 %. The results revealed that the quality of life score among surgical nurses was not high, and differences were observed in the quality of life score of patients according to gender, age, title, and frequency of night shifts (P < 0.05). There was a positive correlation between occupational stress and job burnout. Higher levels of occupational stress and job burnout were associated with a poorer quality of life score. Occupational stress and job burnout were identified as risk factors for quality of life, and the interaction between high levels of stress and burnout seriously reduced quality of life. The structural equation model revealed that occupational stress and job burnout had a direct impact on quality of life, occupational stress had a direct impact on job burnout, and job burnout was identified as a mediating factor in the relationship between occupational stress and quality of life. Conclusions Surgical nurses have a high level of occupational stress and burnout, and low quality of life score. Quality of life is correlated with occupational stress and job burnout. According to the individual characteristics and psychological state of nurses, managers can implement personalized intervention measures promptly and effectively to relieve their tension and burnout, and improve the quality of life of surgical nurses.